The Effect of Transformational Leadership, Change Management, and Employees Engagement on the Competitive Advantage of the Sailing Polytechnic BPSDM Ministry of Transportation - Umiyatun Hayati Triastuti; Nadiroh Nadiroh; Neti Karnati (International Journal of Education, Information Technology, and Others, 2020)
The objective of this study was to determine the effect of transformational leadership, change management, and employee engagement on competitive advantage. This study used quantitative approach with path analysis techniques. Data was collected by distributing instruments at the Sailing Polytechnic BPSDM Ministry of Transportation. The results of the study were as follows, there were: (1) positive direct effect of transformational leadership on competitive advantage; (2) positive direct effect of change management on competitive advantage; (3) positive direct effect of employees engagement on competitive advantage; (4) positive direct effect of transformational leadership on employees engagement; and (5) positive direct effect of change management on employees engagement.